Urban Governance “Going Native”. European Experiences - Jorna, Frans (University of Wroclaw. Faculty of Law, Administration & Economics, 2013)
This paper traces the characteristics of post-bureaucratic urban governance by providing a cross-country comparative account of innovations in urban governance in three European cities: Almelo (the Netherlands), Potsdam (Germany) and Wrocław (Poland). On the basis of a focused comparison of twenty years of local innovation, it concludes that various trends lead to a convergence of local governance in cities (urban governance) that can be characterized as Participative Urban Governance (PUG). Representative local democracy and local government are gradually transformed into a regional hybrid governance arrangement, where formal local political fora predominantly focus on organizing accountability.
Keywords: zarządzanie miastami; Almelo (Holandia); Poczdam (Niemcy); Wrocław